Explorative pedestrian mobility geolocated data from a citizen science experiment in a neighbourhood - Ferran Larroya; Roger Paez; Manuela Valtchanova; Josep Perelló (Scientific Data)
Abstract Pedestrian geolocated data are key to a better understanding of micro-mobility within a neighbourhood. These data can bring new insights into walkability and livability in the context of urban sustainability. However, pedestrian open data are scarce and often lack a context for their transformation into actionable knowledge in a neighbourhood. Citizen science and public involvement practices are powerful instruments for obtaining these data and take a community-centred placemaking approach. The study shares some 3 000 geolocated records corresponding to 19 unique trajectories made and recorded by groups of participants from three distinct communities (72 participants and 19 groups) in a relatively small neighbourhood. The groups explored the neighbourhood through a number of actions and chose different places to stop and perform various social and festive activities. The study shares not only raw data but also processed records with specific filtering and processing to facilitate and accelerate data usage. Citizen science practices and the data-collection protocols involved are reported in order to offer a complete perspective of the research undertaken jointly with an assessment of how community-centred placemaking and operative mapping are incorporated into local urban transformation actions.